Phase doppler anemometry measurements of multiphase bubble column - Gan, Zhiwen (2013)
Bubble column is widely used in both industrial and environmental applications. In this study, the flow dynamics and stability of both two-phase and three-phase bubble columns were examined using Phase Doppler Anemometry (PDA).